PENERAPAN MANAJEMEN RESIKO BANK, TATA KELOLA PERUSAHAAN DAN KINERJA PERUSAHAAN PERBANKAN INDONESIA - Cahyaningtyas, Susi Retna; Sasanti, Elin Erlina (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
Bank as one of the financial institutions in Indonesia is demanded by its owners and shareholders to have good performance in order to continuously increase the value of the company. In order to improve performance, companies must be able to analyze the risks that might occur by implementing risk management. However, good risk management is not adequate to describe the good performance of banks if the banking sector has not been well implemented the GCG. This study aims to examine the effect of risk management and Good Corporate Governance (GCG) on company performance. Research conducted on companies from the banking sector included in 50 top companies list with highest CG score based on the IICD version in 2017. Risk management in this study is measured by four ratios, namely the NPL ratio to measure credit risk, NIM to measure market risk, LDR to measure risk liquidity and BOPO to measure operational risk. GCG in this study is measured by the results of GCG implementation assessment based on the ASEAN CG Scorecard. ROA and Tobin’s Q, measure the company’s performance as the dependent variable in this study. The results showed that only NPL, NIM and BOPO had a significant effect on company performance that was proxied by ROA and only LDR, BOPO and GCG that had a significant effect on company performance, which was proxied with Tobin's Q.